Switching Time Optimization via Time Optimal Control for Natural Gas Vehicle Refueling - Mahidzal Dahari, Mahidzal (2007)
The implementation of Natural Gas Vehicle (NGV) refueling system using multipressure storage source requires a suitable controller to be developed. In this thesis, a refueling algorithm using Time Optimal Control (TOC) technique is proposed as a basis for determining the optimal switching time in NGV refueling using the mass and mass flowrate as the state variables, measured using Coriolis flowmeter. In order to implement TOC in actual NGV refueling process, a fully instrumented NGV laboratory test facility was designed and commissioned which includes three main parts: the NGV test rig, the Data Acquisition (DAQ) & Control System using FieldPoint, and the LabVIEW programming model. Performance measurements for experiments conducted at NGV test rig are based on two criteria, i. e., the refueling time and the total mass of natural gas stored. These become the performance measurements used to evaluate the performance of TOC and other NGV controller currently applied in the commercial NGV dispenser i. e., Kraus refueling algorithm. The performance of the refueling algorithms are evaluated based on three experiments: the first experiment is the performance of valves switching and refueling time transitions; the second experiment is the performance of refueling when the storage pressures are set to 3600 psig while the receiver tank is varied from 20 to 2000 psig; and the third experiment is the performance of refueling when the storage pressures are set to different pressures while the receiver tank is maintained at 20 psig. In conclusion, the results from the third experiment verifies the viability of TOC refueling compared to Kraus refueling to be used in NGV refueling using multi-pressure storage source, which average difference for refueling time and total mass loss are 25.33 seconds and 0.95 kg, respectively. By implementing the refueling algorithm in actual NGV refueling stations, it is expected to provide saving in term of the energy consumed by the compressor and contributing to the reduction in the NGV station congestion problem in the country.